Hubungan Mutu Pelayanan Keperawatan dengan Kepuasan Pasien di Ruangan IGD RSUD Dr. Slamet Garut - Perceka, Andhika Lungguh (Jurnal Ilmiah Administrasi Publik, 2020)
The level of satisfaction of patients in the ward emergency department Dr Slamet Garut Hospital in health services describes the quality of service in the place of health care. The objective of this Telaahan study is to know the relationship of nursing services with patient satisfaction in the room IGD RSU Dr. Slamet Garut. As for method, it used a descriptive correlational, with a accidental samplingtechnique, the number of samples 67 respondents, the data retrieval technique was carried out using questionnaires. The results showed that (56.7%) Respondents expressed poor nursing service and (86.8%) feel dissatisfied about the nursing service in the IGD room RSU Dr. Slamet Garut. This is because the waiting time and the nurse response is slow in providing service. Nursing services can be improved when supported by competent nursing resources, facilities and infrastructure that support and more quickly in conducting nursing actions.